ANALYSIS STUDENTS’ ANXIETY IN LEARNING SPEAKING USING DRILL METHOD - Juwitawati, Wina; Pratiwi, Andiany Retno (PROJECT (Professional Journal of English Education), 2018)
Speaking skill is one of the most difficult aspects of language learning. Students find it difficult to express themselves in spoken language. This research is to know how far the anxiety students in learning speaking. Anxiety analysis is very important because it will affect the extent to which goals will be achieved. Researchers analyze level of anxiety in learning speaking used drill method and also used FLCAS ( Foreign Language Classroom Anxiety Scale) questionnaire by Howritz et al (1986) for collecting data. The FLCAS data questionnaire consisting of 33 items scoring with Likert’s scale and analyzed manually used Oeting’s scale. The researchers take 20 students from X mipa 1 of SMA Pasundan Cikalongkulon Cianjur in the academic year 2017/2018. In conclusion the research showed that there is a significant and it is difference indicated that drill method was effective in reduced students’ anxiety in learning speaking.Keywords: Speaking, Drill method, Anxiety